Study and application of noncatalyzed photoinduced conjugation of azides and cycloocta-1, 2, 3-selenadiazoles. Issue 26 (9th March 2016) - Jedináková, P.; Šebej, P.; Slanina, T.; Klán, P.; Hlaváč, J.
Abstract : The non-catalyzed cycloaddition of eight structurally different azides with cyclooctyne generated in situ by the photolysis of cycloocta-1, 2, 3-selenadiazole gives 1, 2, 3-triazole derivatives as the main products. Abstract : The non-catalyzed cycloaddition of eight structurally different azides with cyclooctyne generated in situ by the photolysis of cycloocta-1, 2, 3-selenadiazole gives 1, 2, 3-triazole derivatives as the main products. The application of this reaction was demonstrated by the photoconjugation reaction of cycloocta-1, 2, 3-selenadiazole with an avidin-modified biotin complex to introduce a new strategy in the non-catalyzed synthesis of bioconjugates.